Upaya Peningkatan Kesadaran Masyarakat dan Deteksi Dini Diabetes Melitus Melalui Edukasi dan Skrining - Salsabila, Lyansaputri; Rindarwati, Asti Yunia; Destiani, Dika Pramita; Jamaica, Putri Avanny (Institut Riset dan Publikasi Indonesia (IRPI), 2024)
Diabetes mellitus (DM) is a metabolic disease caused by a persistent increase in high blood glucose levels due to insufficient insulin production. Diabetes affects individuals of all ages and genders making it one of the most common global causes of death and disease. The most common types of DM are type 1 and type 2, which are generally caused by impaired insulin secretion and/or insulin action. Before an individual develops type 2 diabetes, the individual previously suffered from prediabetes, a condition where blood glucose levels are higher than normal but not yet high enough to be diagnosed as diabetes. The impact of diabetes can be reduced by taking preventative measures for type 2 diabetes and prediabetes through early detection, appropriate treatment and education regarding diabetes. Counseling activities were carried out at the Regional Health Center, Derwati, Rancasari, Bandung, West Java, Indonesia on June 8 2024, from 84 people who took part in the activity, 15% were in the diabetes category and 15% in the prediabetes category. Providing education and good lifestyle recommendations is carried out to increase public awareness and routine compliance with blood sugar control, which is an important action to maintain disease stability and prevent more serious complications.